Preparation of zinc oxide and poly-ethylene oxide composite membranes and their phase relationship (2012)
Zinc oxide and organic polymer (poly-ethylene oxide) based nanocomposite membranes were prepared and their phase relationship investigated. The composites were characterized by XRD, Raman scattering, DSC, and impedance spectroscopy analysis. It was found that embedding inorganic nanoparticles of ZnO into the polymer matrix of PEO allowed for some crystallinity formation, and cross-linking of the polymer composites during annealing or synthesis. The XRD and Raman scattering results show more defined peaks assigned to each phase of the composite as the ZnO content increases from 0 to 30% weight ratio, thus indicating that ceramic filler remain in the semi-crystalline polymer matrix as a separate crystalline phase. The dc-electrical conductivity increases by two or three orders of magnitude from blank (organic phase only) (~10-6 Scm-1 ) to the 30 % wt. ZnO composite membrane (~10-4 Scm-1 ). Electrical conduction changed as a function of temperature with an Arrhenius-type behavior.